Importance of adherence to BCR-ABL tyrosine-kinase inhibitors in the treatment of chronic myeloid leukemia - Almeida,Maria Helena de (2014)
Treatment of chronic myeloid leukemia with BCR-ABL tyrosine kinase inhibitors requires full adherence in order to maximize the likelihood of achieving optimal responses, and to minimize healthcare costs. In this article, we review some of the methods available for assessing compliance, the main consequences of nonadherence on treatment outcomes, major factors commonly associated with poor compliance, a few successful measures for improving adherence and the most accepted recommendations for proactively managing adverse events.